Presentation of CXCL12γ by heparan sulfate proteoglycans activates CXCR4 without desensitization in normal and malignant B cells - Hildo C. Lantermans; Fangxue Ma; Annemieke Kuil; Martin F. M. de Rooij; Nick D. Bergkamp; Werner van der Meer; Jaap D. van Buul; Martine J. Smit; Marie José Kersten; Marcel Spaargaren; Steven T. Pals (Blood Advances)
Abstract: CXCL12-CXCR4 signaling is involved in a wide variety of homeostatic and pathologic processes, but the role of specific CXCL12 isoforms has remained largely unexplored. We have recently shown that the CXCL12γ isoform, which holds an exceptionally high affinity for heparan sulfate (HS), is produced by human bone marrow stromal cells (BMSCs) and remains cell surface immobilized by HS proteoglycans (HSPGs). This HS-bound CXCL12γ is critical for the adhesion of multiple myeloma cells to BMSCs and for BMSC-mediated drug resistance. In this study, we investigated how CXCL12γ activates and regulates CXCR4 by employing a variety of biosensors in HEK293T cells, endogenous CXCR4-expressing B-lymphoma and myeloma cell lines and primary B cells. We showed that CXCL12γ and CXCL12α bind CXCR4 with a similar affinity and that the cumulative activation of CXCR4 over time is equal for both ligands, although CXCL12α activates CXCR4 more rapidly. Although nonbound CXCL12γ and CXCL12α equally induce CXCR4 internalization, cell- or heparin-bound CXCL12γ hardly induces CXCR4 internalization or desensitization. CXCL12γ presented by HSPGs on the membrane of human bone marrow endothelial cells (HBMECs) induces potent cell adhesion to the endothelium under physiological flow, but cells retain the ability to migrate toward CXCL12α when they encounter HBMEC-bound CXCL12γ. Taken together, our data demonstrate that CXCL12γ and CXCL12α differentially modulate CXCR4 trafficking and that CXCL12γ, when immobilized and presented by HSPGs on the cell surface of HBMECs, can efficiently arrest circulating cells without causing CXCR4 internalization or desensitization, thus enabling subsequent cell migration toward a CXCL12α gradient.